The therapeutic relationship - an analytical perspective (Engrami, 2025)
The most significant factor in therapeutic change is the therapeutic relationship. In this paper, we will consider the specifics of the therapeutic relationship from the perspective of analytical or Jungian psychotherapy. First, we will briefly explain the characteristics of the therapeutic relationship in the classical, archetypal and developmental school of Jungian psychotherapy. We will connect the psychotherapy process with the concept of individuation and in that context we will explain the analytical approach to the symptom as a crisis in the individuation process. Various viewpoints on transference will be presented, from the development of Jung's original ideas to the latest viewpoints on the nature and use of transference and countertransference in therapeutic work. In particular, we will consider the concept of the wounded healer. We could understand this constellation as an archetypal basis for establishing an analytical relationship. Guggenbuhl-Craig extended the concept of the "wounded healer" to the field of all helping professions. This archetype has two poles; the first is manifested through health, power, ability, while the second pole of this archetype is manifested through weakness, illness, passivity, incapacity, dependence. It often happens that only one pole is associated with the role of doctor and psychotherapist. The second pole of the archetype – weakness and illness – is related to the role of the patient. And in fact, the therapist, just like the client, carries within him the potentials of both opposite aspects -health and illness. The wounded healer understands and heals precisely his wound, which never completely heals and represents a common field of experience for both the therapist and the client.We can also understand the recovery process as the process of activating the "inner healer" in our patients. After completion of the therapeutic process, they rely on their inner potential for healing and recovery, which is not only a result of the introjection of the therapist and the therapeutic relationship, but also has its archetypal basis.
Keywords: therapeutic relationship; transference; countertransference; wounded healer